Analisis postur pekerja welder menggunakan metode Ovako Work Analysis System (OWAS) (Studi kasus : PT. Putra Jawamas Surabaya) - Octavia, Eka Anestya; Iriani, Iriani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Putra Jawamas is a company that provides services in the field of repair, fabrication, and procurement, with a primary focus on heavy equipment vehicles. One of the techniques often used in the company's operations is welding, which is a process of joining metals by melting some of the parent metal and filler metal into an inseparable part of operational activities at PT. Putra Jawamas. Therefore, to ensure the health and safety of workers is maintained, supervision of the work environment is needed, especially for workers involved in welding activities. Based on the results of the analysis carried out, it is known that the company obtained a category assessment score of 2, which indicates that there are still areas that need to be improved. Thus, the company is expected to improve working conditions for welding workers in the future. This step is very important to maintain the quality of competent workers, while ensuring the quality of products produced by PT. Putra Jawamas is maintained properly.